Students' Perceptions of Augmented Reality Based Student Worksheets on Circle Geometry - Wulandari, Trisna; Susanti, Ely; Hiltrimartin, Cecil (Universitas Muhammadiyah Surakarta, 2026)
This study aimed to describe students’ perceptions of the use of Augmented Reality (AR)-based student worksheets in learning circle geometry. A descriptive quantitative approach was employed. The participants were 30 eleventh-grade students from a senior high school in Palembang selected using convenience sampling, as they were directly involved in learning activities using AR-based worksheets. Data were collected through a 20-item Likert-scale questionnaire covering cognitive, affective, and psychomotor/social aspects. Students’ responses were analyzed descriptively by calculating the percentage of response frequencies for each Likert-scale category and aspect to identify overall perception trends. The results indicated that most students expressed positive perceptions of AR-based student worksheets, particularly in supporting conceptual understanding, learning engagement, and classroom interaction. However, a considerable proportion of neutral responses was also observed, especially in the affective aspect, indicating variation in students’ emotional engagement. Overall, AR-based student worksheets were perceived as a supportive learning medium for circle geometry learning within the context of this study.